Risk and Protective Factors Associated to Peer School Victimization - Méndez, Inmaculada; Ruiz-Esteban, Cecilia; López-García, J. J. (Frontiers in Psychology, 2017)
The main objective of this study is to analyse the relationship between peer school victimization and some risk and protection factors and to compare the differences by role in victimization with those of non-involved bystanders. Our participants were 1,264 secondary students (M = 14.41, SD = 1.43) who participated voluntarily, although an informed consent was requested. A logistic regression model (LR) was used in order to identify the victim’s potential risks and protective factors related to non-involved bystanders. A multiple LR and a forward stepwise LR (Wald) were used. The results showed the variables related to the victim profile were: individual features (to be male, to be at the first cycle of compulsory Secondary Education and a few challenging behaviours), school environments (i.e. school adjustment), family environment (parental styles like authoritarianism) and social environment (i.e. friends who occasionally show a positive attitude towards drug consumption and easy access to drugs, access to drugs perceived as easy, rejection by peers or lack of social acceptance and social maladjustment). The results of the study will allow tackling prevention and intervention actions in schools, families and social environment in order to improve coexistence at school and to assist the victimized students in the classroom.